The mediating role of perceived social capital on the relations of perceived organizational virtuousness and socially responsible leadership withemployee well-being - BÜLBÜL, SEÇİL (My University, 2022)
Nowadays, employees’ well-being has become an important subject of research since the concept of employee well-being is essential in terms of economic, social, and psychological levels for an organization and individuals. The aim of this study is to examine the relationship of employee wellbeing with perceived organizational virtuousness and socially responsible leadership while testing the mediating role of perceived social capital in these relationships. To rationalize the proposed model, an online survey is used to collect the data of 11 employees from various sectors in Istanbul/Turkey. Firstly, descriptive statistics, as well as factor and reliability analyzes are performed. Afterwards, correlation and regression analyses are run to test the model. According to the results, perceived organizational virtuousness and socially responsible leadership are positively associated with employee well-being. In addition, it is revealed that social capital has a mediating role in both relations. The recommendations for leaders and researchers are to give more importance to the concepts at the level of organization and leader to increase employees’ well-being and to carry out practices for creating social capital in organizations.

Çalışan iyi oluşu kavramının, bir örgüt ve/veya bireyler için ekonomik, sosyal ve psikolojik faktörler açısından önem taşıması günümüzde önemli bir araştırma konusu haline gelmiştir. Dolayısıyla, bu çalışmanın amacı, çalışan iyi oluşu kavramının algılanan örgütsel erdemlilik ve sosyal sorumluluk temelli liderlik ile ilişkisini incelemek ve ayrıca her iki ilişkide sosyal sermaye algısının aracı rolünü test etmektir. Önerilen araştırma modelini uygulamak ve analiz etmek için İstanbul/Türkiye’deki çeşitli sektörlerden 311 çalışandan çevrimiçi anket yoluyla örnekleme ulaşılmıştır. Modeli test etmek için tanımlayıcı istatistikler, faktör ve güvenirlik analizleri, korelasyon analizi ve regresyon analizi yapılmıştır. Araştırma sonuçlara göre, algılanan örgütsel erdemlilik ve çalışan iyi oluşu arasında, ayrıca sosyal sorumluluk temelli liderlik ve çalışan iyi oluşu arasında da pozitif ilişkiler bulunmuştur. Diğer bir yandan, sosyal sermayenin her iki ilişkide de aracılık rolü olduğu ortaya konmuştur. Çalışmanın uygulamaya yönelik ve teorik katkıları arasında, çalışanların iyi oluşlarını artırmak için örgüt ve lider düzeyindeki kavramlara daha fazla önem verilmesi ve örgütlerde sosyal sermaye oluşturmaya yönelik uygulamaların yapılması sayılabilmektedir.
Keywords: organizational virtuousness; socially responsible leadership; employee well-being; social capital; örgütsel erdemlilik; sosyal sorumluluk temelli liderlik; çalışan iyi oluşu; sosyal sermaye.